Antenatal Cytomegalovirus Infection Screening Results of 32, 188 Patients in a Tertiary Referral Center: A Retrospective Cohort Study. (4th March 2019) - Sert, Yasemin; Ozgu-Erdinc, A. Seval; Saygan, Sibel; Engin Ustun, Yaprak
Abstract: Objective: The present study aimed to determine cytomegalovirus (CMV) seroprevalence, low and high avidities, and the frequency of polymerase chain reaction (PCR) positivity and neonatal disease in an obstetric population. Materials and methods: Sera of 32, 188 women were tested for CMV IgM and/or CMV IgG between 2008 and 2017. Those with IgM were tested for antibody avidity. Of those with low avidity, PCR was offered. Results: The frequency of CMV IgG and IgM seropositivity was 62% (16, 759/26, 854) and 22% (74/32, 188). The number with low avidity was 42. In 36/42, the infants were PCR tested for CMV and 9 were CMV positive. Only one infant had signs of congenital CMV infection at the time of birth. Conclusion: This study shows the prevalence of Cytomegalovirus infections in a tertiary referral center in Turkey. Although universal screening is not recommended, it can be helpful for the prevention of congenital infection for seronegative women to be advised to at-risk patients due to high prevalence of CMV exposure.